The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
DOI: 10.33915/etd.2202
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to improve the ovulatory response and reproductive performance of ewes introduced to rams during seasonal anestrus

Abstract: Thesis submitted to the Davis College of Agriculture, Forestry, and Consumer Sciences at West Virginia University in partial fulfillment of the requirements for the degree of Master of Science in Reproductive Physiology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Probably, sheep detect day light changes by means of a bult-in biologic clock in the hypothalamus, and this information is transmitted to the hypothalamus gonadal axis via the pineal gland (Bowen, 2003). Melatonin, a pineal hormone, mediates the response to changes in the photoperiod in sheep (Bowen, 2003), melatonin levels are high during dark period and low during light period, probably these differences in the pattern of melatonin secretion act as a signal indicating day length to the nevroendocrine axis (Jordan, 2005), melatonin which is produced and secreted by the pineal gland exclusively at night, is believed to determine the effects of photoperiod on the cyclic activity of the ewe, along duration of melatonin secretion signals a short-day, where as a short duration of melatonin secretion signals a long day ( Younes, 2008).…”
Section: I11 Seasonality and Ovarian Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Probably, sheep detect day light changes by means of a bult-in biologic clock in the hypothalamus, and this information is transmitted to the hypothalamus gonadal axis via the pineal gland (Bowen, 2003). Melatonin, a pineal hormone, mediates the response to changes in the photoperiod in sheep (Bowen, 2003), melatonin levels are high during dark period and low during light period, probably these differences in the pattern of melatonin secretion act as a signal indicating day length to the nevroendocrine axis (Jordan, 2005), melatonin which is produced and secreted by the pineal gland exclusively at night, is believed to determine the effects of photoperiod on the cyclic activity of the ewe, along duration of melatonin secretion signals a short-day, where as a short duration of melatonin secretion signals a long day ( Younes, 2008).…”
Section: I11 Seasonality and Ovarian Activitymentioning
confidence: 99%
“…As in other species the estrus cycle can be divided into phases. the follicular phase 3-4 days, and the luteal phase that lasts about 14-15 days, which characterized by the maturation of the corpus luteum and high levels of progesterone that reach a maximum peak about 6 days after ovulation (Jordan, 2005).…”
Section: I12 the Estrus Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Ram leads to a rise of the LH concentration in females within a few minutes and later to an increased LH pulse frequency, which is a prerequisite for this method can improve the efficacy of estrus synchronization or induction as well. In this respect, Jordan (2005) reported that introduction of rams to ewes induced ovulation, and this method is referred to as the ram or male effect. This effect allows induction breeding during anestrus and produce some of synchrony of cycle among the ewes in flock (Chanvallon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%